Hidróxidos duplos lamelares: nanopartículas inorgânicas para armazenamento e liberação de espécies de interesse biológico e terapêutico Layered double hydroxides: inorganic nanoparticles for storage and release of species of biological and therapeutic interest - Vanessa R. R. Cunha; Ana Maria da C. Ferreira; Vera R. L. Constantino; Jairo Tronto; João B. Valim (Química Nova, 2010)
Studies about the inorganic nanoparticles applying for non-viral release of biological and therapeutic species have been intensified nowadays. This work reviews the preparation strategies and application of layered double hydroxides (LDH) as carriers for storing, carrying and control delivery of intercalated species as drugs and DNA for gene therapy. LDH show low toxicity, biocompatibility, high anion exchange capacity, surface sites for functionalization, and a suitable equilibrium between chemical stability and biodegradability. LDH can increase the intercalated species stability and promote its sub-cellular uptake for biomedical purposes. Concerning the healthy field, LDH have been evaluated for clinical diagnosis as a biosensor component.